The Importance of Servicescape in The Digital Industry Era - Sari, Maya Permata; Afifah, Afifah; Gustina, Gustina; Novadilastri, Novadilastri (ABEC Indonesia, 2024)
Servicescape or service environment is a variable that defines the availability of tangibles where services areprovided to consumers. In the service business, the physical condition of the place where the service is provided caninfluence consumer perception and satisfaction. Servicescape is one of the most critical aspects in adding value to customersbecause business players need to provide satisfaction and value to customers. The objects of this research activity areAmbient Condition, Spatial Layout, Functionality, Sign Symbol, and Artifact, with the unit of analysis being the consumersof Workas Coffee and Eatery. This research model is qualitative, and data collection is conducted using a questionnairethat includes open-ended questions. Data analysis was performed using Nvivo Version 12 to assist in coding therespondents' answers. The coding results indicate that 50% of respondents highlighted aspects of the servicescape ofWorkas Coffee and Eatery, such as limited parking area, insufficient indoor cooling, a lack of electrical outlets, and lightingissues.